Surface-Engineered Graphene Quantum Dots Incorporated into Polymer Layers for High Performance Organic Photovoltaics - Kim, Jung Kyu; Kim, Sang Jin; Park, Myung Jin; Bae, Sukang; Cho, Sung-Pyo; Du, Qing Guo; Wang, Dong Hwan; Park, Jong Hyeok; Hong, Byung Hee (NATURE PUBLISHING GROUP, 2015)
Graphene quantum dots (GQDs), a newly emerging 0-dimensional graphene based material, have been widely exploited in optoelectronic devices due to their tunable optical and electronic properties depending on their functional groups. Moreover, the dispersibility of GQDs in common solvents depending on hydrophobicity or hydrophilicity can be controlled by chemical functionalization, which is particularly important for homogeneous incorporation into various polymer layers. Here we report that a surface-engineered GQD-incorporated polymer photovoltaic device shows enhanced power conversion efficiency (PCE), where the oxygen-related functionalization of GQDs enabled good dispersity in a PEDOT:PSS hole extraction layer, leading to significantly improved short circuit current density (J(sc)) value. To maximize the PCE of the device, hydrophobic GQDs that are hydrothermally reduced (rGQD) were additionally incorporated in a bulk-heterojunction layer, which is found to promote a synergistic effect with the GQD-incorporated hole extraction layer.
Keywords: HETEROJUNCTION SOLAR-CELLS; CONDUCTING POLYMER; HOLE EXTRACTION; ACTIVE LAYER; OXIDE-FILMS; DEVICES; EFFICIENCY; NANOPARTICLES; TRANSPARENT; ENHANCEMENT